ANALYSIS OF THE IMPACT OF THE ENACTMENT OF THE HEALTH LAW ON THE NATIONAL HEALTH INSURANCE SYSTEM (JKN) - Gunawan Widjaja; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (Adisam Publisher, 2025)
This study aims to analyse the impact of the enactment of the 2023 Health Law on the governance and sustainability of the National Health Insurance System (JKN) in Indonesia. The method used is a literature review by examining various laws and regulations, policy documents, and relevant previous research results. The analysis results indicate that although the provisions that directly alter the structure and authority of the Health Social Security Agency (BPJS Kesehatan) were ultimately not adopted in the final draft of the Health Law, the regulatory dynamics still raise concerns regarding the potential for bureaucratic intervention, reduced independence of BPJS, and overlapping authority between managing agencies and ministries. Additionally, regulatory changes require adjustments in coordination between BPJS Health, the Ministry of Health, and healthcare facilities to ensure quality, equitable access, and the sustainability of JKN financing. This study recommends the need for strengthened governance, regulatory harmonisation, and independent oversight to ensure that the primary objectives of JKN—fair and sustainable health protection for all Indonesian citizens—are achieved optimally.